Implementing systems medicine within healthcare. Issue 1 (December 2015) - Kirschner, Marc; Bauch, Angela; Agusti, Alvar; Hilke, Sebastian; Merk, Sibylle; Pison, Christophe; Roldan, Jim; Seidenath, Bernard; Wilken, Michael; Wouters, Emiel; Mewes, Hans-Werner; Heumann, Klaus; et al.
Editorial summary The cause of a complex disease cannot be pinpointed to a single origin; rather, a highly complex network of many factors that interact on different levels over time and space is disturbed. This complexity requires novel approaches to diagnosis, treatment, and prevention. To foster the necessary shift to a pro-active systems medicine, proof-of-concept studies are needed. Here, we highlight several systems approaches that have been shown to work within the field of respiratory medicine, and we propose the next steps for broader implementation.